2017
DOI: 10.1080/15389588.2017.1285022
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and driving and perceptions of arrest risk among California drivers: Relationships with DUI arrests in their city of residence

Abstract: Objective Addressing drinking and driving remains a challenge in the U.S. The present study aims to provide feedback on DUI in California by assessing if drinking and driving behavior is associated with the DUI arrest rates in the city in which the driver lives; if this is through perceptions that one can get arrested for this behavior; and if this differed by those drivers who would be most affected by deterrence efforts (those most likely to drink outside the home). Methods This study consisted of a 2012 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Surveys on alcohol and drugs on drivers provide valuable information on abuse patterns and trends, which help to establish new examination methods and legal limits as well as preventative measures. Numerous surveys on driving under the influence of alcohol and drugs were conducted worldwide through analyzing data from traffic offences and accidents as well as from roadside testing [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] ]. The surveys revealed that in addition to alcohol, drugs including cannabis, amphetamines and cocaine were frequently taken by the drivers, while polydrug uses were not rare.…”
Section: Surveillance In Toxicologymentioning
confidence: 99%
“…Surveys on alcohol and drugs on drivers provide valuable information on abuse patterns and trends, which help to establish new examination methods and legal limits as well as preventative measures. Numerous surveys on driving under the influence of alcohol and drugs were conducted worldwide through analyzing data from traffic offences and accidents as well as from roadside testing [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] ]. The surveys revealed that in addition to alcohol, drugs including cannabis, amphetamines and cocaine were frequently taken by the drivers, while polydrug uses were not rare.…”
Section: Surveillance In Toxicologymentioning
confidence: 99%
“…
The current data from The National Center for Statistics and Analysis (NCSA) Fatality Analysis Reporting System (FARS) shows that, in Los Angeles County, 670 deaths were involved in a motor vehicle traffic crash in 2018 [1]. There is evidence that some drivers in California have accepted the practice of drinking and driving [2] even though there is a perceived high risk of arrest [3,4]. This situation may actually be underestimated due to underreporting of actual alcoholimpaired driving [5].Los Angeles County has a population size of just over 10 million inhabitants.
…”
mentioning
confidence: 99%